2024
DOI: 10.3847/1538-4357/ad38bb
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Nature of Little Red Dots and what Is Not, MIRI SMILES Edition

Pablo G. Pérez-González,
Guillermo Barro,
George H. Rieke
et al.

Abstract: We study 31 little red dots (LRD) detected by JADES/NIRCam and covered by the SMILES/MIRI survey, of which ∼70% are detected in the two bluest MIRI bands and 40% in redder MIRI filters. The median/quartiles redshifts are z = 6.9 5.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 93 publications
1
7
0
Order By: Relevance
“…The SED of Cerberus is, in fact, very similar to the LRDs recently presented and characterized in a number of papers (e.g., Labbé et al 2023bLabbé et al , 2023aMatthee et al 2024;Barro et al 2024;Williams et al 2024;Pérez-González et al 2024;Kokorev et al 2024), but shifted to longer wavelengths. Based on detections of Cerberus in stacked images, we can infer that the F277W − F444W > 1 mag general selection criterion of LRDs and, more specifically, the 3 mag color of the example source 203749 in Pérez-González et al (2024) compare well, if we multiply the observed wavelengths by a factor of ∼2, with F444W − F1000W ∼ 3.5 mag, or, using the F560W 5σ upper limit, F560W − F1000W  2 mag.…”
Section: Multiwavelength Photometrysupporting
confidence: 82%
See 4 more Smart Citations
“…The SED of Cerberus is, in fact, very similar to the LRDs recently presented and characterized in a number of papers (e.g., Labbé et al 2023bLabbé et al , 2023aMatthee et al 2024;Barro et al 2024;Williams et al 2024;Pérez-González et al 2024;Kokorev et al 2024), but shifted to longer wavelengths. Based on detections of Cerberus in stacked images, we can infer that the F277W − F444W > 1 mag general selection criterion of LRDs and, more specifically, the 3 mag color of the example source 203749 in Pérez-González et al (2024) compare well, if we multiply the observed wavelengths by a factor of ∼2, with F444W − F1000W ∼ 3.5 mag, or, using the F560W 5σ upper limit, F560W − F1000W  2 mag.…”
Section: Multiwavelength Photometrysupporting
confidence: 82%
“…The reduction of the MIRI data followed the methodology described in Pérez-González et al (2024), based on the official JWST pipeline (v1.13.4, jwst_1202.pmap) and offline bespoke procedures. Briefly, a superbackground strategy is used to build background maps for each single image using all the other exposures (since they were taken during the same campaign), which results in a very homogeneous background in terms of level and noise.…”
Section: The Mirimentioning
confidence: 99%
See 3 more Smart Citations